Biosorption of zinc(II) ions from aqueous solution using msasa tree (brachystegia spiciformis) leaf powder - Chigondo, Fidelis; Nyambuya, T. (Midlands State University, 2015)
The purpose of this study was to explore the effectiveness of the Brachystegia spiciformis leaf powder for the removal of zinc (II) ions from aqueous solution. Batch experiments for the effect of pH, contact time, biomass dose and initial metal ion concentration were carried out in the laboratory. The adsorbent was characterized before and after biosorption of zinc ions by Fourier Transform-Infrared Spectroscopy (FT-IR). The investigation showed that the highest metal uptake was at solution pH 6, contact time of 120 mins and biomass dose of 2.0 g. The experimental data for the biosorption zinc (II) ions by Brachystegia spiciformis leaf powder was modelled to the Langmuir and Freundlich isotherms. The biosorption of zinc (II) ions fits better to the Langmuir than to the Freundlich model having correlation coefficients of 0.9902 and 0.9569 respectively. The maximum adsorption capacity Qmax was found to be 1.85 mg/g indicating the ability of the biosorbent to remove zinc from aqueous solution.